Arcobacter Butzleri in an AIDS Patient - Trevor Hwee Yong Tan; Sai Meng Tham; Paul Anatharajah Tambyah (Case Reports in Infectious Diseases)
Background. Arcobacter butzleri (A. butzleri) is an emerging enteric pathogen increasingly identified in Europe and is likely under-reported in other global regions. We describe to our knowledge the first case report of A. butzleri in an AIDS patient, along with the first documented local (Singapore) case of A. butzleri infection. Case Presentation. A 38-year-old AIDS patient presented with diarrhoea of 2 weeks’ duration. Stool cultures yielded A. butzleri. The patient was treated with 3 days of ciprofloxacin with clinical resolution of diarrhoea. Conclusion. A. butzleri is likely to be present, although under-reported in AIDS patients, and it should be noted as a pathogen of increasing significance.